The Role of Near-Infrared Spectroscopy (NIRS) in Neurological and Neurodegenerative Diseases as Support to Clinical Practice: An Overview of the Literature - Elvira Gjonaj; Caterina Formica; Emanuele Cartella; Nunzio Muscarà; Silvia Marino; Angelo Quartarone; Simona De Salvo (Diagnostics)
Near-Infrared Spectroscopy (NIRS) is a non-invasive technique that measures the oxygenation variations of brain tissue in response to different stimuli. It has many advantages such as being easy to use, portable, and non-invasive. Several studies over the years have demonstrated the usefulness of NIRS in neurological and neurodegenerative diseases. NIRS remains relatively underutilized in clinical practice. The aim of this brief review was to describe the use of NIRS in neurological and neurodegenerative diseases and how its use can modify clinical, therapeutic, and rehabilitative approaches. A total of 54 relevant articles were selected from the PUBMED research database related to the diagnostic and prognostic role of fNIRS in the main neurological and neurodegenerative diseases; significant outcomes have been reported in a descriptive form with careful considerations. In addition, we excluded studies using fNIRS in co-registration with other neurophysiological techniques. The use of NIRS should be applied even in the field of neurological and neurodegenerative diseases; in dementia, NIRS can aid in differential diagnosis and predict possible evolutions from Mild Cognitive Impairment (MCI) to Alzheimer’s Disease (AD) stage; in stroke, it plays an important role especially in the post-acute phase, giving information about the patient’s chances of recovery; in Parkinson’s Disease (PD), the results showed the important role of cognitive aspects; in epilepsy, NIRS can localize the epileptic focus or potentially predict seizure onset.